Using Interactive Management to Identify, Rank and Model Entrepreneurial Competencies as Universities' Entrepreneurship Curricula. (March 2014) - Rezaei-Zadeh, Morteza; Hogan, Michael; O'Reilly, John; Cleary, Brendan; Murphy, Eamonn
While the strong influence of entrepreneurial competencies on business performance is recognised, despite some doubts about the teachability of these competencies, a fundamental question has remained unanswered: what are the key entrepreneurial competencies that need to be developed in an entrepreneurship curriculum and how are these competencies interrelated? The current study used Interactive Management (IM) with a group of seven successful entrepreneurs to identify, clarify, rank order and build a consensus model describing the interdependencies between 12 entrepreneurial competencies. Results indicated that positivity and competitiveness are fundamental drivers of all other competencies in the consensus model. At the same time, determination and inquisitiveness were the most highly ranked competencies. Results are discussed in light of the ongoing challenges of defining the optimal scope and sequence of training in entrepreneurial curricula. This article fulfils an identified need to study specific entrepreneurial competencies that are to be promoted in university students.